In vitro metabolic N- and C-oxidation of phenanthridine - (:unkn) unknown (MEDECINE ET HYGIENE, 1997)
The in vitro microsomal metabolism of phenanthridine has been studied to establish as to whether phenanthridine produces the corresponding N-oxide and lactam as metabolites and the mechanism involved, We now report our preliminary findings using rat hepatic microsomal preparations (control and induced with phenobarbitone) fortified with NADPH. The potential metabolite, phenanthridine-N-oxide, was prepared by m-CPBA oxidation of substrate; the lactam was commercially available. The substrate and metabolites were extracted and analysed by HPLC and TLC. Five metabolites, i.e. the corresponding N-oxide, lactam and three other products, were detected. Both N-oxide and lactam metabolites showed identical chromatographic behaviour and UV spectrum - using a multi-array UV detector linked to a HPLC system - as the authentic compounds. The uncharacterised metabolites are proposed to be phenolic because of their chromatographic behaviour and response to detection reagents. The amount of N-oxide and lactam formed was significantly increased when phenobarbitone induced rat microsomes were used as enzyme source. The results indicate that these latter metabolites are probably formed by a phenobarbitone inducible CYP450 isozyme. It may be that the lactam was produced via the N-oxide and experiments are under way to investigate the proposed pathway.
Keywords: phenanthridine; phenanthridine-N-oxide; 2-phenanthridone; microsomes; in vitro metabolism; OXIDES